Relationship among Green Production Benefits: A Causal Model - Mendoza Fong, José Roberto; Díaz Reza, José Roberto; García-Alcaraz, Jorge Luis (2020)
Green production processes are becoming increasingly important, as consumers not only demand quality, economical and durable products, but also products that are environmentally friendly. Manufacturers are therefore wondering how feasible it is to transform their traditional production process into a green production process, since such transformation involves economic investment and the relationship between these two dimensions is unknown. This article presents a model of structural equations where four different types of benefits are associated: process benefits, quality benefits, market benefits, and green benefits that can be obtained by implementing a green production process and facilitating manufacturers' decision making. The model is validated with information from 559 responses from managers who have applied the concepts of green production processes in the Mexican manufacturing industry. The partial least squares technique is used to validate the models and the results indicate that the four benefits have a direct and positive effect on each other and the most significant is that there are process benefits and quality benefits